PI3K-based molecular signatures link high PI3K pathway activity with low ER levels in ER+ breast cancer. (December 2010) - Sanchez, Alex; Villanueva, Josep
Evaluation of: Creighton C, Fu X, Hennessy BT et al. Proteomic and transcriptomic profiling reveals a link between the PI3K pathway and lower estrogen-receptor (ER) levels and activity in ER + breast cancer. Breast Cancer Res. 12, R40 (2010). Resistance to endocrine therapy is a major clinical problem in estrogen receptor (ER) + breast cancer. Endocrine resistance can be caused by multiple mechanisms but unfortunately is not fully understood. The work reported by Creighton et al. investigated whether high PI3K pathway activity decreases ER levels, causing endocrine resistance in ER + breast cancer. They developed two PI3K-based molecular signatures – proteomic and transcriptomic – and discovered that the signatures were associated with low ER levels in a set of 429 ER + breast cancer tumors. Signature-based scoring in tumor samples and functional studies with cancer cell lines suggested that blocking both PI3K and estrogen pathways together could be a good therapeutic approach for ER + breast cancer patients with high growth-factor receptor (GFR) signaling. The results presented in the paper could offer new alternatives for the therapeutic treatment of endocrine-resistant breast cancer.